Glocalizing AfriMEDS: a decolonial, Ubuntu-grounded roadmap for operationalizing global competency standards in African medical education - Nathaniel Mofolo; Priscilla Mpho Jama; Gina Wisker (Frontiers in Medicine, 2026)
Background Training community-responsive physicians for South Africa’s under-resourced rural and peri-urban settings remains a defining challenge for African medical education. The AfriMEDS framework, adopted in 2014, succeeded in establishing a shared national competency vocabulary and in standardizing the technical, medical-expert foundations of undergraduate training; it has not yet, however, authentically integrated Indigenous Knowledge Systems (IKS), Ubuntu ethics, indigenous-language proficiency, or formal partnership with Traditional Health Practitioners (THPs). Competency-Based Medical Education (CBME) implementation, while nationally mandated, remains compliance-oriented rather than genuinely glocalized. Objectives To re-examine documented findings from an existing AfriMEDS evaluation, identify where authentic glocalization is missing, and translate those deficits into an integration framework and transferable transformation roadmap. Methods A three-stage interpretive secondary re-analysis engaged the published outputs of a prior mixed-methods doctoral study at the University of the Free State (UFS) MBChB programme, drawing on survey data from 71 medical interns, interviews with 15 educators, and analysis of six curriculum documents. A decolonial, Ubuntu-informed lens re-synthesized the documented findings onto five AIHS pillars. The resulting framework and roadmap are conceptual and inferential; future community co-validation is required. Results The glocalization gap is both empirical and epistemic. Intern self-reported adequacy fell below the 80% threshold the highest reaching 73.2% for five AfriMEDS roles: Leader-Manager (63%), Community-Based Education (71%), Collaborator (72%), Health Advocate (78%), and Communicator (79%); the Medical Expert role scored highest at 91%. Only 40% of interns felt adequately prepared in indigenous-language communication. All community-based education competency items fell below the 80% threshold. IKS, THP protocols, and Ubuntu ethics were absent or tokenistic in all six institutional documents. Educators identified staff shortages and inadequate CBME teaching preparation as principal structural barriers. The AIHS Integration Framework comprises five pillars: epistemic pluralism, community partnership pedagogy, contextualized assessment, educator capacity building, and decolonial quality assurance, operationalized through a six-step roadmap. Conclusion Glocalizing AfriMEDS is a deliberate move from policy compliance toward epistemic freedom. The proposed framework demonstrates that CBME can be simultaneously globally rigorous and locally pluriversal, positioning indigenous knowledge as a necessary complement to, rather than a replacement for, the biomedical core. It offers African medical schools, the Health Professions Council of South Africa (HPCSA), and Global South partners a transferable roadmap for producing graduates who are globally informed and communally accountable. Phase 2 validation through community co-design, Delphi consensus, and multi-site piloting is proposed as future work.